2014
DOI: 10.1590/s0034-8910.2014048004828
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of child undernutrition and stunting in semiarid region of Brazil

Abstract: OBJECTIVETo analyze the evolution in the prevalence and determinants of malnutrition in children in the semiarid region of Brazil.METHODSData were collected from two cross-sectional population-based household surveys that used the same methodology. Clustering sampling was used to collect data from 8,000 families in Ceará, Northeastern Brazil, for the years 1987 and 2007. Acute undernutrition was calculated as weight/age < -2 standard deviation (SD); stunting as height/age < -2 SD; wasting as weight/height < -2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
40
5
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 13 publications
(19 reference statements)
10
40
5
6
Order By: Relevance
“…On the other hand the finding of this study is in contrary to the result of many other previous studies conducted elsewhere [12,19,21,22,24].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand the finding of this study is in contrary to the result of many other previous studies conducted elsewhere [12,19,21,22,24].…”
Section: Discussioncontrasting
confidence: 99%
“…The odds of stunting were significantly higher in male children than female counterparts which are consistent with previous studies [9][10][11][12][13][14][15][16][17][18][19][20][21]. This may be attributed to diseased status during the study period.…”
Section: Discussionsupporting
confidence: 89%
“…[13][14][15][16]29 A metaanalysis of 16 demographic and health surveys from Sub-Saharan Africa observed that boys were more vulnerable to inequalities in health, especially in families with low socioeconomic status. 13 Moreover, the conclusion from 131 demographic health surveys and 48 multiple indicator cluster surveys from 80 countries done from 1990 to 2011 was that countries with higher prevalence of stunting tended to have larger socioeconomic inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…6,14 Children born with low birth weight had a risk of neurological abnormalities that led to poor growth. 14 However, a Filipino study showed that the effect of low birth weight on stunting was strongest during the first 6 months of age, then declined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation